Value Updating Strategies of Kahf, the First Indonesian Muslim Men’s Grooming Brand: A Branderpreneurship Framing Analysis - Giyono Giyono; Bambang S. Wijaya (Jobmark: Journal of Branding and Marketing Communication, 2025)
In increasingly competitive and culturally dynamic markets, brands must continuously renew their value propositions to remain relevant. This study examines how Kahf, an Indonesian Muslim men's grooming brand, implements an updated value strategy through the lens of Branderpreneurship Framing Analysis. This framework integrates entrepreneurial agility with strategic branding. The research aims to analyze how Kahf adapts its brand values in response to evolving consumer expectations, technological change, and lifestyle trends. A descriptive qualitative approach was employed, using secondary data from the brands official website, social media platforms including Instagram, TikTok, and YouTube, as well as press releases and digital publications. The data were analyzed thematically to identify patterns of value updating across branding practices. The findings reveal that Kahf consistently renews its brand value across five key dimensions: product innovation grounded in halal and nature-inspired formulations, expansion of multi-channel distribution, personalized consumer engagement, creative digital storytelling with spiritual and motivational themes, and adaptive business model development within a growing digital ecosystem. These integrated strategies enable Kahf to strengthen its competitive positioning while redefining contemporary Muslim lifestyle branding. Theoretically, this study advances branding and marketing communication literature by operationalizing updating value within a branderpreneurship perspective. Practically, it provides insights for values-driven brands on balancing authenticity and innovation to build resilient, future-ready brand identities.